Analysis of the Influence of Social Media on the Educational Development of the Youth - Dian Rahayu (Enigma in Education, 2023)
The advent of social media has revolutionized the manner in which students engage in communication, access information, and establish connections, thereby exerting an impact on the shaping of their values, ethics, and conduct. Social media is a communication platform that enables students to participate in many online activities, including expressing thoughts and ideas and communicating with others globally. Nevertheless, it is important to acknowledge that the influence of social media can differ significantly, encompassing both advantageous and detrimental effects that must be taken into account when considering the development of students' character. The literature search was conducted across multiple databases, including PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar, to investigate the influence of social media on students' character development. The influence of social media on the development of students' character is highly relevant within the realm of contemporary education. Social media offers a wide range of information and knowledge while also enabling pupils to cultivate communication skills, empathy, cooperation, and digital ethics. Nevertheless, it is crucial to keep in mind that there are potential adverse consequences, like addiction, disruptions in sleep patterns, and mental health problems, that must be taken into account. Educators, parents, and supervisors have a crucial role in providing guidance to kids regarding the prudent and acceptable utilization of social media. It is important for them to offer instruction on digital etiquette, essential skills for organizing information, and effective time management. By adopting a well-rounded strategy, social media can serve as a potent instrument in molding students' character, fostering the cultivation of constructive principles, enhancing their interpersonal abilities, and facilitating a more profound comprehension of the global landscape. Hence, comprehensive education in the digital age has the potential to cultivate astute, compassionate, and accountable individuals within virtual and physical communities.